Pharmaceutical Terminology in Ancient and Medieval Time – "Andrachne", "Chrysocolla" and Others - Zipser, Barbara; Scott, Andrew C.; Allkin, Robert; Gan, Peretz; Lardos, Andreas; Lazarou, Rebecca; Lev, Efraim; Nesbitt, Mark; Patmore, Kristina (Studia Ceranea, 2023)
Ancient and medieval pharmacological and medical texts contain a substantial amount of plant and mineral names. In some cases, the identification is straightforward. But for the majority of the data, we are unable to identify these ingredients with high certainty. In this paper, we discuss a selection of plant and mineral names both from a humanities and sciences point of view. In one case, the scientists were even able to examine a plant in situ. The conclusion of our paper is that a close collaboration between sciences and humanities is essential to avoid mistakes in the identification of materia medica.